KEEFEKTIFAN PERKULIAHAN DARING PADA MASA COVID-19 DI PRODI PENDIDIKAN BAHASA INDONESIA UNIVERSITAS MALIKUSSALEH - Safriandi Safriandi; Syahriandi Syahriandi; Radhiah Radhiah; Trisfayani Trisfayani (Jurnal Dedikasi Pendidikan, 2021)
The purpose of this study was to analyze the effectiveness of online learning at the Indonesian Language Education Study Program, Malikussaleh University. This type of research is a combination research (mixed methods) qualitative and quantitative. The population of this study were all students of the Indonesian Language Education Study Program that follows online learning for the 2020/2021 school year. As for the total number of students in the Pend. Indonesian is 300 people. Because of the large population, in this study a random sample was determined. The results found 130 samples (respondents). The data collection technique of this research was carried out by online survey method using a questionnaire instrument through Google Form. The data analysis technique used is the technique proposed by Miles and Huberman. The results of this study indicate that online learning in the Indonesian Language Education Study Program, Malikussaleh University has not been effective. This is indicated by the acquisition of an average value for each indicator, which is <60%. Students prefer face-to-face learning to be carried out immediately after this pandemic ends.